Magnetic Resonance Imaging Predictors of Failure in the Nonoperative Management of Ulnar Collateral Ligament Injuries in Professional Baseball Pitchers. (July 2017) - Frangiamore, Salvatore J.; Lynch, T. Sean; Vaughn, Michael D.; Soloff, Lonnie; Forney, Michael; Styron, Joseph F.; Schickendantz, Mark S.
Background: A medial ulnar collateral ligament (UCL) injury of the elbow is an increasingly common injury in professional baseball pitchers. Predictors of success and failure are not well defined for the nonoperative management of these injuries. Purpose: To evaluate the efficacy of objective measures to predict failure of the nonoperative management of UCL injuries. Study Design: Case-control study; Level of evidence, 3. Methods: Thirty-two professional pitchers (82%) met inclusion criteria and underwent an initial trial of nonoperative treatment for UCL tears based on clinical and radiological findings. Age, preseason physical examination results, magnetic resonance imaging (MRI) characteristics, and performance metrics were analyzed for these pitchers. Successful nonoperative management was defined as a return to the same level of play or higher for >1 year. Failure was defined as recurrent pain or weakness requiring a surgical intervention after a minimum of 3 months' rest when attempting a return to a throwing rehabilitation program. Results: Thirty-two pitchers (mean age, 22.3 years) who underwent initial nonoperative treatment of UCL injuries were evaluated. Thirty-four percent (11/32) failed and required subsequent ligament reconstruction. Sixty-six percent (21/32) successfully returned to the same level of play for 1 year without a surgical intervention. There was no significant difference seen in physical examination findings or performance metrics between these patients. When comparing MRI findings between the groups, 82% (9/11) ( P < .001) who failed nonoperative management had distal tears, and 81% (17/21) who did not fail had proximal tears ( P < .001). When adjusting for age, location, and evidence of chronic changes on MRI, the likelihood of failing nonoperative management was 12.40 times greater ( P = .020) with a distal tear. No other variable alone or in combination reached significance. When combining the parameters of a high-grade tear and distal location, 88% (7/8) failed nonoperative management. Conclusion: In professional pitchers, distal UCL tears showed significantly higher odds of failure with nonoperative management compared with proximal tears. Thus, tear location should be considered when deciding between operative and nonoperative management.